ANALYSIS OF CALCULATION OF COST OF PRODUCTION (Case Study: Pak Mitro Tofu Making Business in Stabat District, Langkat Regency, North Sumatra) - Jahari, Harmeita; Rozalina, Rozalina; Basriwijaya, Kiagus M. Zain (Syarif Hidayatullah State Islamic University Jakarta, 2024)
This research aims to analyze the cost of production in the Pak Mitro tofu making business in Stabat District, Langkat Regency, North Sumatra. This research uses a case study method and is analyzed quantitatively descriptively. The data collection methods used are primary data and secondary data. The sampling technique used was purposive sampling technique. The subject in this research is the owner of a tofu making business, namely Mr. Mitro. The analysis calculated uses the full costing method and the activity based costing (ABC) method. The results obtained from this research are the cost of production using the Full Costing method of Rp. 269 and using the Activity Based Costing method of Rp. 260. So that the tofu production produced by Pak Mitro's business experiences quite large costs of Rp. 9/unit.